ZAKAT DAN KEADILAN SOSIAL: ANALISIS TERHADAP KITAB AL-AMWAL KARANGAN ABU UBAID - Nasution, Muhammad Syafril; Razali, Ramadhan (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2021)
This research discusses the concept of zakat in Abu Ubaid's Kitab Al-Amwal. The purpose of this study is to analyze the existence of social justice in zakat. The research method that I use is a qualitative method with a literature review method. The result of this research is that zakat according to Abu Ubaid has esoteric values of social justice. Zakat instruments can alleviate poverty and stabilize state finances. To create social justice, the zakat instrument provides space for those in need. The space is not only a treasure. But also capital that can be used to start a business. In addition, in order to optimize zakat, the government must take part in maximizing the potential of zakat.